QUALITY EVALUATION OF POZA BITTERS, A NEW POLY HERBAL FORMULATION IN THE NIGERIAN MARKET - Elufioye, Taiwo Olayemi; Awosika, Oluseyi Arabela (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Development of a quality assurance system for new botanicals for health and nutrition is challenging. Producers must understand consumer demands and develop methods of production that meet those demands of product quality and efficacy, which exceeds or corresponds to international standards. The present article is an attempt to evaluate the quality of Poza bitters, a new polyherbal formulation, used as a purgative, by physical and analytical methods. Materials and Methods: Poza bitters was screened for the presence of secondary metabolites and microbial contamination. The pH, micronutr-ient and heavy metal composition analysis, as well as chromatographic fingerprinting using thin layer chromatography and high performance liquid chromatography were also carried out. Results: Phytochemical analysis revealed the presence of alkaloids, saponins, tannins, and flavonoid glycosides. The pH value was 3.66. The sample assayed had acceptable level of microorganisms and toxic metals were absent. Thin layer chromatography of the sample using methanol/water/acetic acid (30:70:5) showed three spots with Rf values similar to some of references used. High performance liquid chromatography fingerprint showed two retention times of poza bitters which were not similar to those of the reference standards: hesperidin and narigenin, thus suggesting the absence of these flavonoids in poza bitters. Conclusion: Poza bitters comply with WHO microbial standard as well as standards for heavy metals. Also, the presence of Aloe ferox and citrus was confirmed on TLC.